Perfunctory performance of self-compacting concrete using recycled coarse aggregate with and without processing - Srikanth, N.; Murthy, N.R. Dakshina; Rao, M.V. Seshagiri (Journal of Structural Engineering, 2024)
Usage of Recycled Coarse Aggregate (RCA) in construction industry is the need of the era to achieve sustainability. To improve the performance of RCA, adhered mortar is removed by different physical and chemical treatments. This study investigates the practice of processed RCA in Self-Compacting Concrete (RCASCC) for replacement levels (0%, 25%, 50%, 75% and 100%) by abrasion for 500 and 1000 revolutions. The objective of the study is to optimize the number of revolutions and the replacement percentage of processed RCA in the mixes A and B. The study includes the mechanical parameters such as compression, split tension, flexure and bond strengths. Further, to understand and compare the stiffness behaviour of processed and unprocessed RCASCC, stress strain relationship is examined. From the findings it was observed that, with increase in the number of revolutions the performance of processed RCA is decreasing. Also, the results showed a relative improvement in performance of SCC mixes for 500 revolutions at 50% replacement level when compared to unprocessed RCASCC. The outcomes of the study facilitates an experimental evidence for the use of processed RCASCC in structural applications and fulfil the need of replace and reuse of construction demolition waste for achieving sustainability.